Teaching English Grammar in an Indonesian Junior High School - Agis Andriani; Vani Dwi Yuniar; Fuad Abdullah (STAI Hubbulwathan Duri, 2021)
English grammar has a pivotal position in language learning. It is also considered the basis of a series of language skills (listening, speaking, reading, and writing). However, although previous studies focused on teaching English grammar either from a traditional or functional view, where English as L1 and L2 across various educational levels, scarce studies have emphasized teaching English Grammar in the Indonesian EFL context, particularly in Junior High School. Hence, this study aimed at filling such a void, namely teaching English grammar in an Indonesian junior high school. In an attempt for collecting the data, this study interviewed a participant in one of the junior high schools in Tasikmalaya, West Java, Indonesia. The data were analyzed using thematic analysis (Braun Clarke, 2006). The findings of this study revealed that the teacher use focus on forms and focus on form in teaching English grammar. Those focus on forms involve (1) Deductive English Teaching Grammar, (2) Score-Oriented English Language Learning Activities, and (3) Accuracy-Oriented English Language Learning Activities. Another approach is focus on form include (1) Task-Based Sentence Making and (2) Contextual Teaching of English Grammar. By knowing these teaching techniques, the teachers are expected to be able to implement those teaching techniques of teaching English grammar to junior high school students more effectively.